KOMUNIKASI DUA ARAH ANTARA ORANG TUA DAN ANAK DALAM MENGATASI DAMPAK NEGATIF GAME ONLINE OLEH SISWA DI BATU NANGGAR - Noviyana Dila Sari Lubis; Lies Utami Efni Safitri (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
This study aims to describe the forms and processes of two-way communication between parents and children and to analyze students’ responses and behavioral changes in addressing the negative impacts of online gaming. A qualitative descriptive approach was employed to provide an in-depth understanding of the phenomenon based on participants’ experiences. The research was conducted at SMPN 1 Dolok Batu Nanggar involving students and parents selected through purposive sampling. Data were collected through in-depth interviews and observations and analyzed using the interactive model of Miles and Huberman. The findings reveal that two-way communication occurs through stages of emotional approach, open dialogue, and mutually agreed guidance. Dialogic communication patterns foster openness, trust, and more harmonious relationships between parents and children. However, variations such as combined and one-way communication patterns are still found and influence the effectiveness of interactions. Students’ responses to two-way communication indicate positive changes in emotional, cognitive, and behavioral aspects. These changes include increased self-awareness, reduced gaming intensity, and greater openness in communication with parents. Nevertheless, behavioral changes are not entirely stable due to peer influence and the level of consistency within the family. A supportive and communicative family environment strengthens the effectiveness of communication. This study highlights that two-way communication is an effective strategy in addressing the negative impacts of online gaming, yet it requires consistency and sustained environmental support.   Keywords: Two-way Communication, Family Communication, Online Games, Child-Behavior